Emotional labor as the underlying mechanism in the relationship between emotional stability and affective commitment: A study in the hospitality industry - Siwa Kantha Subhiksa; Debora Eflina Purba (Jurnal Manajemen dan Pemasaran Jasa, 2021)
This study aims to examine the mediating effects of emotional labor variables, namely emotive effort and dissonance resulting from deep and surface acting strategies, which are based on the relationship between emotional stability and affective commitment. 249 data were obtained from the hospitality industry in major cities in Indonesia and were analyzed using a mediation technique. The results showed that emotive effort mediated the relationship between emotional stability and affective commitment. Furthermore, it was also shown that emotive dissonance did not mediate the relationship between emotional stability and affective commitment.